Techno-Economic Assessment of Grid Sales Constraints on Solar Power Plants Through Capacity Sizing: A Case Study of Türkiye - Sait Gazi Yildirim; Ali Durusu (IEEE Access)
The integration of solar power plants into the electrical grid poses significant challenges, particularly with regard to the sale of excess energy. Inadequately defined tariffs and regulatory scopes can lead to either excessive investment profitability or technical issues affecting grid security. Regulatory frameworks play a crucial role in shaping the feasibility and profitability of solar projects. Until recently, the high purchase guarantees under Türkiye’s feed-in tariffs have led to excessive profitability for many producers with low consumption, making solar power plants a highly lucrative investment. To address this issue, a significant regulatory change has been introduced, linking the amount of electricity sold to the amount consumed. As a result, a substantial decline in revenues is expected for numerous power plants. This article examines how the regulatory and technical constraints limiting the sale of excess energy to the grid in Türkiye will impact solar power plants and alter the feasibility of new projects. It explores how restrictions imposed by regulatory authorities influence the optimal sizing of solar investments using technical and financial metrics. Various scenarios are analyzed, including capacity limits, demand profiles, net metering periods, and grid sales constraints, to assess their impact on solar plant design. The findings of this study demonstrate that sales restrictions significantly affect the economic viability and technical configuration of solar projects. Compliance with these regulations often requires adjusting plant size to align generation capacity with permissible sales volumes. The study first establishes that the regulatory change has resulted in substantial revenue losses for existing solar power plants and subsequently provides a framework for structuring future investments. The research concludes with recommendations for optimizing the size of solar power plants under electricity sales-constrained conditions across different scenarios to maximize economic benefits. The results demonstrate that with proper sizing, investment returns can be nearly as high as those in unconstrained sales conditions.